KEBUTUHAN CINTA DAN KASIH SAYANG: PRESPEKTIF HIERERKI MASLOW DALAM PERILAKU ARIS DI FILM IPAR ADALAH MAUT - Moh. Rif'an Hidayatullah; Anas Ahmadi (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
Humans, as social beings, have a fundamental need for love and affection that is important for their psychological well-being. This study explores how the fulfillment of this need is portrayed through the character Aris in the film “Ipar adalah Maut” (Brother-in-Law Can Be a Curse). The purpose of this study is to describe the fulfillment of love and affection within the hierarchy of needs in Abraham Maslow's humanistic psychology theory. A qualitative descriptive method was used, with the film “Brother-in-Law Can be a Curse” as the primary data source. Data were collected through literature review and observation-note techniques. The findings of the study show that the need for love and affection in the character Aris is fulfilled through his social interaction with Rani, his sister-in-law. The fulfillment of these needs is evident from the closeness that is established because they live in the same house, the intensity of meetings on campus, and the attention and emotional support given by Rani, especially when Aris's need for affection is not fully fulfilled by his wife, Nisa. This illustrates the shift in the object of Aris's affection, which has an impact on the dynamics of the relationship in the story.